Knowledge of antibiotics and antibiotic resistance, antibiotic use and eHealth literacy among nursing students in Thailand: a cross-sectional study - Soontaree Jianvitayakij; Atsadaporn Niyomyart; Chuenjit Junsawang; Wunwisa Bualoy; Nipaporn Butsing; Supreeda Monkong; Joachim G Voss (BMJ Open)
Objectives Antibiotic resistance poses a major global public health threat. However, research on this issue is limited, especially among nursing students. This study aims to examine knowledge of antibiotics and antibiotic resistance, antibiotic use, and eHealth literacy in Thailand.Design A cross-sectional study was conducted using an online self-administered questionnaire. The WHO Antibiotic Resistance: Multi-Country Public Awareness Survey and the eHealth Literacy Scale were used. Descriptive and multiple regression analyses were performed.Setting Thailand’s North, South, Central and Northeast between January and February 2024.Participants A total of 1180 nursing students aged 18 or older, from first to fourth year and fluent in Thai, were invited to participate.Results The participants were mostly female (89.8%), with an average age of 20.64±1.81 years. Over half of the respondents (67.7%) have used antibiotics, mistakenly believing that antibiotics could treat colds and influenza (70.3%), malaria (66.8%), measles (63.6%) and sore throats (60.9%). About 71.5% recognised the impact of antibiotic resistance on themselves and their families, but 93.1% incorrectly believed antibiotic resistance means the body resists antibiotics. Participants scored 35.92±4.21 out of 40 on eHealth literacy. In a multiple regression analysis, three factors predict knowledge of antibiotic resistance: knowledge of antibiotics (B=0.199, p<0.001, 95% CI 0.165 to 0.234), eHealth literacy (B=0.078, p<0.001, 95% CI 0.056 to 0.100) and academic year (B=0.271, p<0.001, 95% CI 0.184 to 0.358), with knowledge of antibiotics being the most impact (β=0.318). These three variables explained 23.7% of the variance in antibiotic resistance knowledge scores.Conclusions Despite high eHealth literacy, nursing students hold misconceptions about antibiotic treatable conditions and insufficient knowledge of antibiotic resistance. This highlights the need to integrate antibiotic contents into nursing curricular and enhance eHealth literacy for better access and navigate health information.